2014
DOI: 10.1017/s204017441400049x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological changes in laterodorsal tegmental neurons associated with prenatal nicotine exposure: implications for heightened susceptibility to addict to drugs of abuse

Abstract: Prenatal nicotine exposure (PNE) is a risk factor for developing an addiction to nicotine at a later stage in life. Understanding the neurobiological changes in reward related circuitry induced by exposure to nicotine prenatally is vital if we are to combat the heightened addiction liability in these vulnerable individuals. The laterodorsal tegmental nucleus (LDT), which is comprised of cholinergic, GABAergic and glutamatergic neurons, is importantly involved in reward mediation via demonstrated excitatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 109 publications
3
17
0
Order By: Relevance
“…Further, PNE treatment was associated with lower activity-dependent intracellular calcium rises in putative cholinergic LDT cells of juvenile mice, assessed by single-photon calcium imaging of neurons activated by high current injection (Polli and Kohlmeier, 2018), which was an effect attributed to a reduced functionality of voltage-gated calcium channels (VGCCs). This finding is consistent with kinetic alterations seen in the action potential of the PNE LDT found in two independent studies from our laboratory (Christensen et al, 2015;Polli and Kohlmeier, 2018), as lower calcium rises mediated by VGCCs predict smaller activation of calcium-dependent potassium channels, with subsequent broadening of the action potential half-width (Bean, 2007), which were characteristics of the kinetics of the action potential observed in PNE LDT cells. Changes in VGCCs leading to reduced activity-dependent calcium predict a reduced excitability of these neurons, which parallels previous studies showing that PNE LDT neurons displayed a higher rheobase which is the amount of current necessary to induce an action potential (Christensen et al, 2015).…”
Section: Intrinsic Plasticity: Pne and The Action Potentialsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, PNE treatment was associated with lower activity-dependent intracellular calcium rises in putative cholinergic LDT cells of juvenile mice, assessed by single-photon calcium imaging of neurons activated by high current injection (Polli and Kohlmeier, 2018), which was an effect attributed to a reduced functionality of voltage-gated calcium channels (VGCCs). This finding is consistent with kinetic alterations seen in the action potential of the PNE LDT found in two independent studies from our laboratory (Christensen et al, 2015;Polli and Kohlmeier, 2018), as lower calcium rises mediated by VGCCs predict smaller activation of calcium-dependent potassium channels, with subsequent broadening of the action potential half-width (Bean, 2007), which were characteristics of the kinetics of the action potential observed in PNE LDT cells. Changes in VGCCs leading to reduced activity-dependent calcium predict a reduced excitability of these neurons, which parallels previous studies showing that PNE LDT neurons displayed a higher rheobase which is the amount of current necessary to induce an action potential (Christensen et al, 2015).…”
Section: Intrinsic Plasticity: Pne and The Action Potentialsupporting
confidence: 91%
“…This finding is consistent with kinetic alterations seen in the action potential of the PNE LDT found in two independent studies from our laboratory (Christensen et al, 2015;Polli and Kohlmeier, 2018), as lower calcium rises mediated by VGCCs predict smaller activation of calcium-dependent potassium channels, with subsequent broadening of the action potential half-width (Bean, 2007), which were characteristics of the kinetics of the action potential observed in PNE LDT cells. Changes in VGCCs leading to reduced activity-dependent calcium predict a reduced excitability of these neurons, which parallels previous studies showing that PNE LDT neurons displayed a higher rheobase which is the amount of current necessary to induce an action potential (Christensen et al, 2015). Consistent with this, in unpublished observations, we noted that while PNE LDT neurons displayed higher inward currents upon AMPA application in the absence of TTX, a significantly smaller percentage of neurons fired action potentials following AMPAR activation in the PNE group relative to the number of cells in which AMPA induced action potential firing in control.…”
Section: Intrinsic Plasticity: Pne and The Action Potentialsupporting
confidence: 91%
“…In addition, although reductions in cellular excitability in the VTA have been reported following PNE, as well as inhibition of release of DA to target structures (Alkam et al, 2013a, 2013b), other studies have found enhanced DA neural activity, suggestive of heightened excitability in PNE rodent offspring (Zhang et al, ). We have shown that cholinergic signaling in a brain stem cholinergic group which provides excitatory glutamatergic and the majority of cholinergic input to the VTA is altered by PNE, suggesting a role for this alteration in behavioral outcomes associated with PNE (Christensen et al, ; McNair and Kohlmier, ). In our continuing goal of elucidating neural changes associated with early life exposure to nicotine, we wished to test our hypothesis that AMPAR‐ and nAChR‐based excitability is altered in the VTA in PNE animals, reflected as alterations in AMPAR and nAChR‐stimulated rises in intracellular calcium.…”
Section: Introductionmentioning
confidence: 98%
“…By bulk loading LDT cells with Fura-2-AM and conducting dynamic fluorescent imaging to indirectly assess changes in calcium, muscimol, and baclofen were used to activate cellular activity via actions at GABA A Rs and GABA B Rs, and a novel ligand, 1, was used to assay activity at GABA Aρ R, a subclass of GABA A R, in female and male brain slices prenatally exposed to nicotine or saccharine. As age-related differences in PNE effects are known to be present in the LDT, we conducted our study in cells collected within two age groups (Christensen et al, 2015). All three ligands were associated with changes in fluorescence indicative of decreases and increases in intracellular calcium levels in the majority of recorded cells in both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Given its connectivity, changes induced by PNE in the LDT could influence behaviors regulated by mesolimbic, mesocortical, and thalamic pathways. PNE-associated LDT functional changes have been demonstrated for nAChRs, glutamatergic receptors, voltage-operated calcium channels (VOCCs), and neuronal membrane properties (Christensen, Nielsen, & Kohlmeier, 2015;McNair & Kohlmeier, 2015;. Changes in excitability were shown to be age-dependent, which would be layered upon ontologically-appropriate developmental shifts in cellular distribution (Ninomiya, Kayama, & Koyama, 2005).…”
mentioning
confidence: 99%